Keabsahan Penerbitan Izin Usaha Pertambangan di Kabupaten Konawe Kepulauan - Mirdan Mirdan; Rudy Iskandar Ichlas; Nur Nashriany Jufri; Wahyudi Umar (Jurnal Hukum Lex Generalis, 2024)
This study examines the legality of the IUP issuance process in Konawe Islands Regency, identifies potential administrative and legal violations, and provides recommendations to strengthen regulatory compliance. The research method used is normative juridical with a legal and case study approach. The results show that most IUPs in Konawe Islands Regency are issued without meeting administrative requirements, such as adequate environmental studies and consultations with affected communities. In addition, inconsistencies were found in the licensing process, such as procedural violations by the authorities that caused conflicts of interest and losses to the local community. This shows that there is a gap in the supervision and implementation of regulations.